The complex social and legal context of the use of live birds in Mexico - Roldán-Clarà, Blanca; Leyva, Claudia; Espejel, Ileana; López-Medellín, Xavier (Ethnobiology and Conservation, 2021)
The use of song and ornamental birds (SOB) as pets is a traditional and commercial activity in Mexico. This paper is part of a larger research which aim was to analyze the commercial use of birds. The objective is to depict the complexity of the stake-holders system involved in the activity of live birds selling in Mexico. We display in diagrams the main stakeholders involved in the activity, highlighting stakeholders acting in several or three spatial scales (micro- or regional, meso- or national, and macroor global) and the extent of their influence in management. Depicting the complexity in the use of SOB is essential to better understand the decision-making process and improve it in the future.